2005
DOI: 10.1152/ajpgi.00519.2004
|View full text |Cite
|
Sign up to set email alerts
|

Secretin differentially sensitizes rat pancreatic acini to the effects of supramaximal stimulation with caerulein

Abstract: Supramaximal stimulation of the rat pancreas with CCK, or its analog caerulein, triggers acute pancreatitis and a number of pancreatitis-associated acinar cell changes including intracellular activation of digestive enzyme zymogens and acinar cell injury. It is generally believed that some of these various acinar cell responses to supramaximal secretagogue stimulation are interrelated and interdependent. In a recent report, Lu et al. showed that secretin, by causing generation of cAMP and activation of PKA, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…MAPK modules are known to be transiently activated during cerulein-induced pancreatitis (25)(26)(27)(28)(29)(30)(31). Inhibition of these modules has been associated with an improvement in the outcome during AP (27,(39)(40)(41). By analyzing these pathways in our mouse model, we also detected a prolonged activation of MAPK modules (ERK1/2 [p42/44], p38, and SAPK [p46/54]) during inflammation in the rela Δ/Δ pancreas (Figure 4).…”
Section: Figurementioning
confidence: 69%
“…MAPK modules are known to be transiently activated during cerulein-induced pancreatitis (25)(26)(27)(28)(29)(30)(31). Inhibition of these modules has been associated with an improvement in the outcome during AP (27,(39)(40)(41). By analyzing these pathways in our mouse model, we also detected a prolonged activation of MAPK modules (ERK1/2 [p42/44], p38, and SAPK [p46/54]) during inflammation in the rela Δ/Δ pancreas (Figure 4).…”
Section: Figurementioning
confidence: 69%
“…To assess the interaction between TRX-1 and secretory response of pancreatic acinar cells, we studied whether amylase secretion from acinar cells treated with CER could be influenced either by TRX-1 overexpression in the pancreas or treatment with rhTRX-1. Pancreatic acinar cells were obtained from the pancreas of WT or TRX-1-TG mice by collagenase treatment as described previously (2,3,34,49,52). These cells were incubated with various concentrations of CER (10 Ϫ12 -10 Ϫ7 M) for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In pancreatic acinar cells, secretin as well as other agents that increase cAMP have little effect on zymogen activation alone but sensitize the response of agents that increase intracellular calcium such as cerulein or cholecystokinin (11,12). In pancreatic acini, it was reported that a cell-permeable cAMP inhibitor (Rp-8Br-cAMP) reduces the sensitization induced by vasoactive intestinal peptide and 8Br-cAMP to low and high doses of cerulein (11).…”
Section: Blockade Of Multidrug Resistance-associated Proteins Aggravamentioning
confidence: 99%